SPEECH ERRORS IN ENGLISH AS A FOREIGN LANGUAGE ON SOUTH KOREAN TV SHOW "MY ENGLISH PUBERTY 100 HOURS" - Nuruzzakiyyah Yahya (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
Abstract The speech errors in the South Korean TV show "My English Puberty 100 Hours" are examined in this study. Using Clark & Clark and Fromkin's theory, the researcher investigates many speech errors. Researchers pioneered the speech error patterns of artists by studying the types of speech errors. In addition to these two aspects, the researcher used Clark & Clark's theory to investigate the reasons for speech errors. The qualitative descriptive analysis method is used in this study. The data was gathered from the English utterances of the artists who took part in the television show "My English Puberty 100 Hours." After watching the video numerous times, the researcher created a transcript to collect data. The researcher found that two speech errors, namely silent pause and interjection, did not show their presence in the study. Meanwhile, the researcher could not find four types of a slip of the tongue, including anticipation, preservation, misderivation/shift, and haplologies/blend. The researchers found that in the television show "My English Puberty 100 Hours," artists frequently make speech errors. A repeat is a form of speech error that artists frequently exploit. The most common types of a repeat are phrases and function words in pronouns. Artists make speech errors for various reasons, depending on the circumstances. Cognitive difficulties, situational anxiety, and social circumstances all play a role in each artist's reasoning.